Pengembangan Bahan Ajar Practice Set Akuntansi Perusahaan Dagang Berbasis Flipbook untuk Kelas XI Akuntansi - Damayanti Indraswari; Joni Susilowibowo (Jurnal Pendidikan Akuntansi (JPAK), 2022)
This development research aims to develop flipbook-based practice set teaching materials for trading company accounting, assess feasibility, and analyze student responses to develop flipbook-based practice set teaching materials for trading company accounting. The ADDIE model is used in this R&D research with the stages of analysis, design, development, implementation, and evaluation. Twenty students from class XI AKL SMK Negeri 1 Surabaya participated in the research. The expert validity results obtained a recapitulation of the average feasibility 0f 90,93% with a very feasible interpretation. Material experts scored 84,68% with very decent interpretation, language experts scored 88,10% with very decent interpretation, and graphic experts scored 100% with very decent interpretation. The student’s reaction to the product demonstrates that the criteria are well understood with a percentage of 96,15%. The obtained conclusions refer to the study’s findings that this teaching material is very suitable for use as a learning resource for students. Suggestions for further research are expected to be able to validate the evaluation of the questions so that the presentation of the questions is of higher quality and conduct trials not only in one school.